2016
DOI: 10.1016/j.semcancer.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Promise of bitter melon ( Momordica charantia ) bioactives in cancer prevention and therapy

Abstract: Recently, there is a paradigm shift that the whole food-derived components are not ‘idle bystanders’ but actively participate in modulating aberrant metabolic and signaling pathways in both healthy and diseased individuals. One such whole food from Cucurbitaceae family is ‘bitter melon’ (Momordica charantia, also called bitter gourd, balsam apple, etc.), which has gained an enormous attention in recent years as an alternative medicine in developed countries. The increased focus on bitter melon consumption coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 108 publications
(186 reference statements)
0
66
0
3
Order By: Relevance
“…The advantages of exploiting their chemopreventive and therapeutic efficacy are the minimal associated toxicities to surrounding normal healthy cells and cost effectiveness; particularly with PanC, there have been extensive studies connecting dietary agents to reduced PanC incidences . BMJ, a dietary agent extracted from the fruits of Momordica charantia , has numerous associated health benefits; antidiabetic, emetic and laxative . Studies using BMJ/BMJ‐extracts in animals show lower serum cholesterol levels, hypoglycemia and delayed onset of tumorigenesis, alongside improved glucose tolerance in human subjects without significant alterations to insulin levels with BMJ administration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of exploiting their chemopreventive and therapeutic efficacy are the minimal associated toxicities to surrounding normal healthy cells and cost effectiveness; particularly with PanC, there have been extensive studies connecting dietary agents to reduced PanC incidences . BMJ, a dietary agent extracted from the fruits of Momordica charantia , has numerous associated health benefits; antidiabetic, emetic and laxative . Studies using BMJ/BMJ‐extracts in animals show lower serum cholesterol levels, hypoglycemia and delayed onset of tumorigenesis, alongside improved glucose tolerance in human subjects without significant alterations to insulin levels with BMJ administration .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using BMJ/BMJ‐extracts in animals show lower serum cholesterol levels, hypoglycemia and delayed onset of tumorigenesis, alongside improved glucose tolerance in human subjects without significant alterations to insulin levels with BMJ administration . Component analysis of bitter melon characterizes all the important constituents with multiple beneficial effects, mainly cucurbitane‐type triterpenoids, triterpene glycoside, phenolic acid, flavonoids, essential oils, fatty acids, saponins and amino acids . The toxicity data is minimal with only evident side effects being diarrhea and abdominal pain that can be relatively easily managed .…”
Section: Discussionmentioning
confidence: 99%
“…BME displayed anticancer activities in various cancer models (1013). In addition to its direct inhibitory effect on tumor growth and survival, BME also has demonstrated immunomodulatory activity in a syngeneic mouse model of HNSCC by inhibiting Treg activity (14).…”
Section: Discussionmentioning
confidence: 99%
“…Bitter melon ( Momordica charantia ) is extensively cultivated in Asia, Africa, and South America, and is widely used in folk medicines to treat diabetes (9). In our previous studies, we demonstrated that BME is effective in killing various types of solid tumors including head and neck cancer (1013). We found that BME inhibits HNSCC cell proliferation through modulation of c-Met signaling in in vitro as well as in vivo using a xenograft model (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that MAP30 exhibits a variety of anti-infection, anti-diabetic, antiviral and antitumor bioactive effects (4)(5)(6)(7)(8)(9)(10). The antitumor ability of MAP30 has been the subject of previous studies (11)(12)(13)(14)(15). However, certain researchers have already noted the effects of MAP30 on the inhibition of U87 cells in screening for anticancer effects (3,7,16,17).…”
Section: Introductionmentioning
confidence: 99%